PEMBELAJARAN AKUNTANSI PERBANKAN MENGGUNAKAN MODEL PEMBELAJARAN CIRC - Budi Mulyati; Reni Febriani; Mimin Mintarsih (FKIP, Universitas Banten Jaya, 2021)
The aim of this research was to developed the learning planning using cooperative integrated reading and composition (CIRC) for teaching basic banking subject in vocational school level. The method in this research used R&D method and using ADDIE model (Analysis, Design, Develop, Implement, Evaluate). But in this research, researcher did not use the Evaluate phase because this research did not measure the effectiveness. The study indicated that based on the results of experts assessments (teacher and lecturer) the learning planning obtain value up to 4,35 and 3,95. Meanwhile, based on the students responses obtain value up to 3,9. So it could be concluded that in general the assessment of learning planning using CIRC Model obtain the good result. Teacher or school could also use this learning planning with CIRC model to teach the students in subject of basic banking for vocational school level.